IMPLEMENTASI PLTS UNTUK MEMBINA KADER MASYARAKAT SURABAYA YANG SADAR ENERGI HIJAU - Lanny Agustine; Yuliati Yuliati; Rasional Sitepu; Albertus K Martin; Brian H Santosa; Camala K Subiantoro; Diana Lestariningsih; Peter R. Angka (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2023)
Residents of RT 03 RW 03 Tambakrejo Village, Simokerto District, Surabaya City have begun to realize the benefits of green energy and are motivated to develop solar power plant implementations for various needs. Community service activities were attended by 11 residents. Activities include the addition of a solar power plant system and decorative lights to develop existing systems, and the implementation of rat repellents in the hydroponic area electronically. This activity aims to train and educate residents through assistance in solar power plant installations, making decorative lights and applying rat repellents with the water spray method. Based on observations during the solar power plant installation process and the manufacture of decorative lights, it appears that participants have become familiar with the constituent components, installation steps and practical testing of the solar system. The commitment and enthusiasm of residents and local leaders has been demonstrated by the ability to produce varied forms of decorative lights and the contribution of providing poles and solar panel boxes. The rat repellent system with the water spray method was also observed to be effective so that hydroponic plants were free from rat interference.